G77 A Case of Dilated Cardiomyopathy Due to Nutritional Vitamin D Deficiency Rickets. (4th June 2013) - Babu, P; Damda, F
Abstract : Introduction: Dilated Cardiomyopathy is an important cause of heart failure in children. It often has an idiopathic aetiology, but may also be caused by infection and can be inherited. Hypocalcaemia is a rare but important reversible cause of dilated cardiomyopathy. Vitamin D deficiency is the main cause of hypocalcaemia in almost all reported cases. Case Report: An 8 month-old, Afro-Caribbean boy, presented with acute heart failure and respiratory distress. He was born in the UK and exclusively breastfed until 6 months of age. Cardiovascular examination revealed a gallop rhythm and a grade 2/6 pan systolic murmur at the apex, with a 2cm liver edge palpable. There was clinical evidence of rickets. Investigations included a chest X-ray, which showed cardiomegaly and plethoric lung fields. ECG showed increased left ventricular voltages and a prolonged QTc interval. Venous blood gas revealed a metabolic acidosis and a low ionised calcium level (0.6mMol/l). Echocardiogram revealed a poorly functioning and dilated left ventricle with severe mitral regurgitation. Hypocalcaemia secondary to severe vitamin D deficiency was diagnosed by screening blood tests. In addition to supportive treatment for cardiac failure (furosemide and captopril) he was treated with alphacalcidiol and Calcium-Sandoz. Echocardiogram 2 months later showed a near normal left ventricular function with a well contracting ventricle. His biochemical profile normalised within 4 weeks of treatment. Discussion: Nutritional vitamin D deficiency leading to dilated cardiomyopathy has been increasingly reported, and indicates it as an important aetiology to consider in heart failure. A recent retrospective review showed that such infants can present in extremis, requiring inotropic and ECMO support. However, compared to other cardiomyopathies, there is a relatively good prognosis, with a mean recovery of left ventricular shortening reported at 12.4 months. 1 Rickets itself has seen a resurgence, especially in developed countries 2 This is a preventable condition, but obstacles 3, 4 have been reported, despite NICE 5 and DoH 6 guidelines for antenatal care, post-natal supplementation and clinical management. Conclusion: This case represents a serious consequence for undiagnosed vitamin D deficiency. In view of its preventable nature, healthcare professionls should have greater awareness. This has been supported by the recent RCPCH position statement calling for practical sign-posting. 7